Penggunaan Media Pembelajaran Jaring-Jaring Bangun Ruang Untuk Peningkatan Minat Belajar Siswa Kelas 2 di SDN 03 Desa Kembang Tanjung - Dewi Ratnaningsih; Nanda Nurraksa Brahma Putra; Naurah Nathania; Usda Tri Mulya; Dinda Ayu Novitasari; Umi Fadilah (Pengabdian Kepada Masyarakat Cendekia, 2022)
This community service program is one of the three Tri Dharma of tertiary institutions which must be carried out. Community service activities entitled KKN UMKO transfer of knowledge are carried out in Kembang Tanjung Village, South Abung District, North Lampung Regency, Lampung Province. This community service activity focuses on education in order to improve learning interest of elementary school students to increase student interest in learning, learning is made more active and productive with learning media nets build space learning media nets build space is a learning media using cut cardboard to form a pattern of nets build space media This learning is expected to be a means to increase student interest in learning and build active and exciting learning.